2014
DOI: 10.1016/j.celrep.2014.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic versus Nonserotonergic Dorsal Raphe Projection Neurons: Differential Participation in Reward Circuitry

Abstract: Summary The dorsal raphe nucleus (DRN) contains the largest group of serotonin-producing neurons in the brain and projects to regions controlling reward. Although pharmacological studies suggest that serotonin inhibits reward-seeking, electrical stimulation of the DRN strongly reinforces instrumental behavior. Here, we provide a targeted assessment of the behavioral, anatomical, and electrophysiological contributions of serotonergic and non-serotonergic DRN neurons to reward processes. To explore DRN heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
168
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(197 citation statements)
references
References 55 publications
(76 reference statements)
21
168
2
Order By: Relevance
“…Given the anatomic interaction of the DA and 5-HT systems, it is important to mention that the response to cocaine observed in the VMAT2 SERTcre mice could also be due to increased DA release. Although a recent study demonstrated that the majority of dorsal raphe neurons that project to the VTA are nonserotoninergic, 46 neuroanatomical studies have revealed 5-HT immunoreactive fibres in the VTA, 47 and there is evidence that the mesolimbic dopaminergic system is under the control of the 5-HT system. 48,49 Alteration of the 5-HT system alters cocaine sensitization As a psychostimulant, cocaine elicits a dose-dependent increase in motor activity in rodents.…”
Section: Differential Roles Of Altered Da and 5-ht Systems On Locomotmentioning
confidence: 98%
“…Given the anatomic interaction of the DA and 5-HT systems, it is important to mention that the response to cocaine observed in the VMAT2 SERTcre mice could also be due to increased DA release. Although a recent study demonstrated that the majority of dorsal raphe neurons that project to the VTA are nonserotoninergic, 46 neuroanatomical studies have revealed 5-HT immunoreactive fibres in the VTA, 47 and there is evidence that the mesolimbic dopaminergic system is under the control of the 5-HT system. 48,49 Alteration of the 5-HT system alters cocaine sensitization As a psychostimulant, cocaine elicits a dose-dependent increase in motor activity in rodents.…”
Section: Differential Roles Of Altered Da and 5-ht Systems On Locomotmentioning
confidence: 98%
“…+ dorsal raphe glutamatergic neuron subgroup projecting to the VTA (Hioki et al, 2010;Liu et al, 2014;McDevitt et al, 2014;Qi et al, 2014). The spared Vglut3 + cells first appeared in the ventral r1 of the Gata2…”
Section: Vglut3mentioning
confidence: 99%
“…The subtypes of serotonergic neurons are interesting from the perspective of behaviour and psychiatric disease. Vglut3-expressing serotonergic and glutamatergic neurons innervate dopaminergic neurons in the VTA and are important for reward signalling (Liu et al, 2014;McDevitt et al, 2014;Qi et al, 2014). Sert is the target of selective serotonin reuptake inhibitors (SSRIs), the commonly used antidepressants.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Two other studies report that optogenetic stimulation of DRN neurons drives reward behavior and emphasizes the contribution of glutamate (McDevitt et al 2014;Qi et al 2014 Stimulating axonal fibers from VGluT3+ neurons results in glutamate release and activates VTA mesoaccumbens dopamine neurons in brain slices. In addition, optogenetic stimulation of DRN VGluT3 neurons reinforces instrumental behavior and establishes conditioned place preference, suggesting the strong potential of glutamate neurons in reward signaling (Qi et al 2014).…”
Section: Optogenetics Reveal Two Different Roles Of Drn Neurons In Rementioning
confidence: 99%